A power-efficient acquisition front end for the Li-ion battery management systems. (November 2022) - Bao, Yuanxin; Ye, Le
Abstract: This paper presents a Coulomb sensing method-based power-efficient acquisition front-end (AFE) for Li-ion battery management systems (BMSs). The AFE, based on two self-calibrated incremental analog-to-digital converters (ADCs), measures the instant current flows in and out of the Li-ion battery, the cell voltage, and the internal and external temperature of the chip to compensate for the state of charge. A switched-capacitor CMOS bandgap reference (BGR) is proposed to obtain stable reference voltage over an operating temperature range of the BMS. A wake-up comparator indicates that a large charging and discharging current occurs while the BMS is in sleeping mode. This solution significantly reduces the obtained samples and has better power efficiency than an always-acquisition method. A prototype was fabricated in the 110-nm CMOS process, achieving a DNL of −0.85/+1.7 LSB and an INL of −3.2/+4.2 LSB. The total current consumption of the normal operation and the sleeping mode from a battery is 23 μ A and 1.26 μ A, respectively.